Extraction of selected bioactive compounds from averrhoa bilimbi and their thermal stability during spray drying - Norlia, Muhamad (2017)
A. bilimbi (ver. name Belimbing Buluh) contains many useful bioactive compounds leading to various activities such as antioxidant, anti-diabetic and anti-tuberculosis. Analysis of the A. bilimbi extracts using UHPLC-QTOF-MS, qualitative analysis and identification using Metlin Database shows the presence of three compounds; nicotinic acid, pantothenic acid and catechin. Following the mass spectrometry and UV spectra confirmation, the nicotinic acid, pantothenic acid and catechin can be used as a marker of A. bilimbi. Recovery of bioactive compounds from the plant materials are normally performed via extraction. The yield of bioactive compound in the extract is dependent on the solvent used, extraction method and condition. In this work, ultrasonic assisted extraction was studied. The highest extraction yields of 0.28 mg/g DW nicotinic acid, 1.00 mg/g DW pantothenic acid and 0.22 mg/g DW catechin from A. bilimbi were obtained at temperature of 30 °C, sonication power of 0.070 W/ml, time of 30 min, solvent to solid ratio of 8 ml/g and methanol concentration of 40%. Bioactive compounds are known to suffer from a degradation process when exposed to high temperature over a long period, which is often the case during the extraction and powder making process. The recovery process is often accomplished at slightly elevated temperatures, thus it is vital to understand the loss of bioactive compounds due to thermal degradation before the mitigating method can be formulated. The results showed nicotinic acid, pantothenic acid and catechin degradation followed the firstorder kinetics model. Pantothenic acid showed the lowest degradation rate constant, followed by nicotinic acid and catechin for all studied temperature, indicating a slowest degradation. The thermal degradation activation energy of nicotinic acid, pantothenic acid and catechin were 43.85 kJ/mol, 58.86 kJ/mol, and 21.27 kJ/mol, respectively. Pantothenic acid has the highest activation energy which implies that the compound is more sensitive to temperature change. Microencapsulation can provide a physical barrier between the core compound and the other components of the product which would then provide a better heat protection during spray drying. Microencapsulation of bioactive compounds from A. bilimbi by spray drying using maltodextrin resulted in a high retention of nicotinic acid, pantothenic acid and catechin. Results obtained from this work demonstrated that the best operating conditions for spray drying of A. bilimbi extract whereby the highest retention of nicotinic acid, pantothenic acid and catechin are 10% maltodextrin DE18 and air inlet temperature 140 °C.